2018
DOI: 10.3847/1538-4357/aae083
|View full text |Cite
|
Sign up to set email alerts
|

SMASHing the LMC: A Tidally Induced Warp in the Outer LMC and a Large-scale Reddening Map

Abstract: We present a study of the three-dimensional (3D) structure of the Large Magellanic Cloud (LMC) using ∼2.2 million red clump (RC) stars selected from the Survey of the MAgellanic Stellar History. To correct for line-of-sight dust extinction, the intrinsic RC color and magnitude and their radial dependence are carefully measured by using internal nearly dust-free regions. These are then used to construct an accurate 2D reddening map (165 deg 2 area with ∼10 resolution) of the LMC disk and the 3D spatial distribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
125
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 89 publications
(169 reference statements)
12
125
2
Order By: Relevance
“…For example, asHelmi et al (2018) suggests, if the dynamical centre were fixed as the photometric centre fromvan der Marel (2001), then the their proper motion would be (1.890, 0.314)mas yr −1 . For Carbon Stars, the best-fitting configuration parameter θ agrees well with other works listed in the table, and i agrees closely with the purely geometric measurement fromInno et al (2016) andChoi et al (2018) .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…For example, asHelmi et al (2018) suggests, if the dynamical centre were fixed as the photometric centre fromvan der Marel (2001), then the their proper motion would be (1.890, 0.314)mas yr −1 . For Carbon Stars, the best-fitting configuration parameter θ agrees well with other works listed in the table, and i agrees closely with the purely geometric measurement fromInno et al (2016) andChoi et al (2018) .…”
supporting
confidence: 86%
“…For example, in the SMC, the gas outflow found by McClure-Griffiths et al (2018) and the shell of young stars recently studied by Martinez-Delgado et al (2019) are both indicative of possible interactions with the LMC. For the LMC, Choi et al (2018) recently identified an outer warp in the disk, and a tilted bar, using red clump stars, consistent with a close encounter with the SMC (see also, Besla et al 2012;Noël et al 2013;Guglielmo et al 2014;Carrera et al 2017;Zivick et al 2019, etc). Joshi & Panchal (2019) found a common enhancement of the Cepheid population in both the LMC and SMC, suggesting an interaction ∼ 200 Myr ago between the Clouds.…”
Section: Velocity Dispersionsmentioning
confidence: 88%
See 1 more Smart Citation
“…2002 ;Peñarrubia et al 2016;Choi et al 2018;Erkal et al 2019). Proper motion studies show that the LMC's disc has a clockwise rotation in the plane of the sky, suggesting an inner region that is relatively "unperturbed" (van der Marel & Kallivayalil 2014;Gaia Collaboration et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic (J − K) 0 color was obtained with the star formation history. Choi et al (2018) measured E(g − i) color excess of the red clump stars covering 165 deg 2 of the LMC disk. To obtain the intrinsic (g − i) 0 color of the red clump, they measured color in the outer regions, assuming negligible internal dust contribution in those fields.…”
Section: Introductionmentioning
confidence: 99%